Nanofibrillar hydrogel scaffolds from recombinant protein‐based polymers with integrin‐ and proteoglycan‐binding domains. Issue 12 (16th August 2016) - Włodarczyk‐Biegun, Małgorzata K.; Werten, Marc W. T.; Posadowska, Urszula; Storm, Ingeborg M.; de Wolf, Frits A.; van den Beucken, Jeroen J. J. P.; Leeuwenburgh, Sander C. G.; Cohen Stuart, Martien A.; Kamperman, Marleen
Abstract: This study describes the design, production, and testing of functionalized variants of a recombinant protein‐based polymer that forms nanofibrillar hydrogels with self‐healing properties. With a view to bone tissue engineering applications, we equipped these variants with N‐terminal extensions containing either (1) integrin‐binding (RGD) or (2) less commonly studied proteoglycan‐binding (KRSR) cell‐adhesive motifs. The polymers were efficiently produced as secreted proteins using the yeast Pichia pastoris and were essentially monodisperse. The pH‐responsive protein‐based polymers are soluble at low pH and self‐assemble into supramolecular fibrils and hydrogels at physiological pH. By mixing functionalized and nonfunctionalized proteins in different ratios, and adjusting pH, hydrogel scaffolds with the same protein concentration but varying content of the two types of cell‐adhesive motifs were readily obtained. The scaffolds were used for the two‐dimensional culture of MG‐63 osteoblastic cells. RGD domains had a slightly stronger effect than KRSR domains on adhesion, activity, and spreading. However, scaffolds featuring both functional domains revealed a clear synergistic effect on cell metabolic activity and spreading, and provided the highest final degree of cell confluency. The mixed functionalized hydrogels presented here thus allowed to tailor the osteoblastic cell response, offering prospects for their further development as scaffolds for bone regeneration. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 104A: 3082–3092, 2016.